Pemberdayaan terhadap Usaha Produktif Umkm melalui Pendekatan Digital Marketing di Desa Ledokombo Kabupaten Jember - Supriono, Agus; Riza Oktafiyani; Rachmat Udhi Prabowo; Julian Adam Ridjal; Ebban Bagus Kuntadi (Yayasan Literasi Sains Indonesia, 2024)
Ledokombo Village is one of the villages in the eastern part of Jember Regency, East Java Province. This village is within the administrative area of Ledokombo District. The area of Ledokombo Village is bordered by the areas of neighboring villages, such as Sukogidri Village, Ledokombo District, and Cumedak Village, Sumberjambe District. One of the elements of society that drives the economy is MSMEs in Ledokombo Village. The MSME players in Ledokombo Village are the